Effect of antibiotic treatment on Oxalobacter formigenes colonization of the gut microbiome and urinary oxalate excretion - Lama Nazzal (Nature Portfolio, 2021)
Abstract The incidence of kidney stones is increasing in the US population. Oxalate, a major factor for stone formation, is degraded by gut bacteria reducing its intestinal absorption. Intestinal O. formigenes colonization has been associated with a lower risk for recurrent kidney stones in humans. In the current study, we used a clinical trial of the eradication of Helicobacter pylori to assess the effects of an antibiotic course on O. formigenes colonization, urine electrolytes, and the composition of the intestinal microbiome. Of 69 healthy adult subjects recruited, 19 received antibiotics for H. pylori eradication, while 46 were followed as controls. Serial fecal samples were examined for O. formigenes presence and microbiota characteristics. Urine, collected serially fasting and following a standard meal, was tested for oxalate and electrolyte concentrations. O. formigenes prevalence was 50%. Colonization was significantly and persistently suppressed in antibiotic-exposed subjects but remained stable in controls. Urinary pH increased after antibiotics, but urinary oxalate did not differ between the control and treatment groups. In subjects not on antibiotics, the O. formigenes-positive samples had higher alpha-diversity and significantly differed in Beta-diversity from the O. formigenes-negative samples. Specific taxa varied in abundance in relation to urinary oxalate levels. These studies identified significant antibiotic effects on O. formigenes colonization and urinary electrolytes and showed that overall microbiome structure differed in subjects according to O. formigenes presence. Identifying a consortium of bacterial taxa associated with urinary oxalate may provide clues for the primary prevention of kidney stones in healthy adults.